Strain-based measurement system on an internal fixator for healing analysis of spinal defects through load redistribution - Steinbild, Philip Johannes; Wieja, Nils; Rodríguez Pino, Luis; Gottwald, Robert; Winkler, Anja; Zwingenberger, Stefan; Disch, Alexander Carl; Schmölz, Werner; Modler, Niels (Frontiers in Bioengineering and Biotechnology, 2025)
A compact measurement system applied to an internal fixator for spinal bony healing is described and its usability for monitoring a simulated healing process on spine models is assessed. Four strain gauges were applied to carbon fiber reinforced polymer (CFRP) rods forming sensor integrated rods in order to measure a multitude of different strains using a minimum of strain gauges. This configuration enables the application not only on CFRP but also on rods made of a different material. Spinal didactic models were instrumented with the sensor rods in combination with pedicle screws in order to depict a bisegmental thoracolumbar stabilisation ranging from spine segments T11 to L1. The transmission of the acquired strain data to an evaluation computer was realized by a customized measurement system using an integrated Bluetooth chip. The measurement system is able to measure isolated bending and tensile or compression strain simultaneously. A standardized fenestration defect was induced at the middle section (T12). To mimic the healing process, three silicone discs of different Shore hardness (0 ShA, 8 ShA, 30 ShA) were inserted into the defect with 0 ShA simulating a fractured T12. A series of three spine models were tested under comparable conditions. Flexion bending moments of 5 Nm were applied to the specimens using a universal testing machine. Isolated bending strain on the rods increased from an unfractured state to the fractured state by 10%–27%. The healed state simulated by a silicone disc of 30 ShA lowered the isolated bending strain reliably for each specimen. Silicone discs of 8 ShA cannot simulate an intermediate healing state reliably.